Metabolic potential of gut microbiota in helminth infections as a way to achieve bronchial asthma control - T. S. Sokolova; V. N. Malchuk; A. D. Zaytseva; O. S. Fedorova; M. R. Karpova (Бюллетень сибирской медицины)
The aim of the review was to analyze modern experimental studies and clinical trials aimed at assessing metabolic activity of gut microbiota in bronchial asthma (BA) and helminth infections.Being one of the most common chronic heterogeneous respiratory diseases, bronchial asthma secures its place among global health problems of great socioeconomic importance. In recent years, a lot of data has been accumulated indicating that the state of gut microbiota is an important factor determining the state of human health and affecting immune mechanisms underlying the development of allergic diseases in childhood. Dysbiosis of gut microbiota is due not only to changes in its composition, but also to disturbances in its metabolism. In accordance with the “gut – lung axis” concept, maintaining healthy gut microbiota and correcting its disorders, including strategies aimed at activating synthesis of short-chain fatty acids in the intestine, may become a new way to prevent and treat chronic respiratory diseases in childhood. In turn, experimental and epidemiological studies have shown the immunomodulatory activity of helminths. It is assumed that their impact on the composition and function of gut microbiota is one of the mechanisms by which helminths influence the immune response of the host and the course of BA.